2014
DOI: 10.3892/mco.2014.377
|View full text |Cite
|
Sign up to set email alerts
|

Survival outcomes and progonostic factors of extrahepatic cholangiocarcinoma patients following surgical resection: Adjuvant therapy is a favorable prognostic factor

Abstract: This study was conducted to investigate survival and prognostic factors for extrahepatic cholangiocarcinoma (ECC) following surgical resection and evaluate the effects of postoperative adjuvant therapy (AT) on overall survival (OS). We retrospectively collected clinical and pathological data between March, 2008 and December, 2013. The Kaplan-Meier method and the COX regression model were used to evaluate the OS and prognostic factors of 105 postoperative ECC patients, of whom 32 had received AT. The patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…patients with positive surgical margins or positive lymph nodes. [61][62][63][64][65][66] Several meta-analyses support adjuvant therapy for the resected disease. 67,68 A systematic review and meta-analysis including 42,917 patients from 35 clinical studies found that there was a significant improvement in OS with any adjuvant therapy after surgery compared with surgery only (HR = 0.74; 95% CI = 0.67-0.83; P < 0.001).…”
Section: Adjuvant Therapymentioning
confidence: 99%
“…patients with positive surgical margins or positive lymph nodes. [61][62][63][64][65][66] Several meta-analyses support adjuvant therapy for the resected disease. 67,68 A systematic review and meta-analysis including 42,917 patients from 35 clinical studies found that there was a significant improvement in OS with any adjuvant therapy after surgery compared with surgery only (HR = 0.74; 95% CI = 0.67-0.83; P < 0.001).…”
Section: Adjuvant Therapymentioning
confidence: 99%
“…There are several studies investigating the effect of systemic chemotherapy combined with local radiotherapy as a modality of AT for patients after radical surgery. [42][43][44][45][46] Most studies are retrospective and remained controversial, because of the small size, the lack of correction for multiple comparisons, heterogeneity in terms of patients' characteristics and so on. 14 Furthermore, the combined patterns of chemoradiotherapy, the technologies of radiotherapy, and the regimens of chemotherapy have not been confirmed.…”
Section: Adjuvant Chemoradiotherapymentioning
confidence: 99%
“…Conversely, a retrospective series of 105 patients with EHCC following surgical resection between March 2008 and December 2013 indicated that AT was not significantly associated with improved OS (HR=0.87, 95% CI, 0.52-1.44, P=0.57). 42 In the study, a total of 32 patients received AT (18 patients chemotherapy, 11 patients radiotherapy, and 3 patients chemoradiotherapy). On subgroup analysis, the patients with pathological lymphatic metastasis demonstrated AT group had a better survival than non-adjuvant therapy group (median OS, 21.6 months vs 10.4 months; and 3-year OS, 16.6% vs 0%, respectively, P=0.02).…”
Section: Adjuvant Chemoradiotherapymentioning
confidence: 99%
“…Extrahepatic cholangiocarcinoma (EHCC), which is a kind of malignant tumor derived from the extrahepatic biliary epithelial cells with high malignant severity and recessive attack, is generally treated with surgeries (Pattanathien et al, 2013;Huai et al, 2014). However, the recurrence is extremely high due to the invasion and metastasis in the early stage of EHCC, which severely threatens patients' prognosis (Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%